A One Health systems approach to the epidemiology, management, and regulatory control of bovine brucellosis at the human-cattle-farm interface in Gauteng, South Africa - Thompson, P.N. (Peter N.) (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2020.